Mental health and psychotherapy: a comparison between Western and Islamic scripturally based psychologies - Abdul Razak, Mohd Abbas; Abdul Razak, Abdul Latif; Ali Zaroum, Abdulhamid Mohamed (IIUM Press, International Islamic University Malaysia, 2019)
Advancement in the way of life and urbanization have brought many great changes in the psychological well-being of people in many parts of the world. The need to be materially affluent has pushed people in the urban settlements to unnecessary stress, anxiety, conflict, dilemma, and a whole lot of other adverse psychological states of mind. Due to these psychological problems, at times, people who mainly live in the cities, respond to these situations in a negative way ignoring completely the religious and ethical principles in life. In light of this situation, this research would like to explore the concepts of mental health and psychotherapy showcased by some selected schools in the Western mainstream psychology and Islamic scripturally based psychology. Particularly, ideas advocated by Freudian Psychoanalysis, Radical Behaviourism and Humanistic Psychology will be compared with Islamic psychology. For a better understanding on issues related to mental health, this research will marginally deal with the subject of human nature confined to the scope of this research. It is hoped that a proper understanding of the concept of mental health and its management could help people to lead a meaningful life, i.e. finding peace and harmony within themselves and in the external world. As a qualitative research, the researchers will utilize the textual-analysis method in analysing relevant data to this research.